KEEFEKTIFAN PJBL DENGAN MEDIA REPLIKA TANGAN TERHADAP KEMAMPUAN KOLABORATIF DAN HASIL BELAJAR PADA PEMBELAJARAN IPA SEKOLAH DASAR - Ari Nur Kristanti; Yayan Ristiana; Siti Inganah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study of human movement systems is often difficult for students to comprehend because it is abstract and theoretical. Therefore, concrete and interactive learning media are needed to help students better understand this concept. This research aims to develop a hand replica as a teaching aid in Science subject for Phase C, focusing on improving students' understanding of the human movement system, particularly the mechanism of bones and muscles.The method used in this study is a classroom experiment employing a pretest and posttest approach, involving students in the creation of hand replicas using simple and easily accessible materials. Students were encouraged to observe, assemble, and manipulate the hand replicas to simulate the movements of a real human hand. Observations showed that the use of hand replicas in learning significantly improved students' understanding of the human movement system. Additionally, using hand replicas helped students develop critical thinking and problem-solving skills through engaging and enjoyable hands-on activities. In conclusion, creating hand replicas as learning media is effective in enhancing students' understanding and collaborative skills in group settings regarding the human movement system in elementary school Science learning. It is hoped that this media can be more widely applied as an innovative method in Science teaching and learning processes.